The Influence of Price, Service Quality, Trust and Product Quality on Scarlett Customer Satisfaction - Erika Tania; Dewi Wuisan; Kyle Christopher Suhail; Danet Arya Patria (Universitas Pelita Harapan, 2024)
This research aims to analyse the influence of price, service quality, trust, and product quality on customer satisfaction for Scarlet products. This research uses a quantitative research approach where data is collected through an online Google Forms questionnaire. This research was conducted in Indonesia and took respondents from Tangerang. The sample in this research was 160 respondents. Data were analysed using the outer model. The outer model consists of validity and reliability tests, while the inner model was tested using R-square, hypothesis testing (bootstrapping), and multicollinearity testing. This research shows that price has a negative and significant effect on customer satisfaction. Meanwhile, service quality, trust and product quality positively and significantly affect customer satisfaction.